COVID-19-Associated Paediatric Inflammatory Multisystem Syndrome (PIMS-TS) in Intensive Care: A Retrospective Cohort Trial (PIMS-TS INT) - Tereza Musilová; Jakub Jonáš; Tomáš Gombala; Jan David; Filip Fencl; Eva Klabusayová; Jozef Klučka; Milan Kratochvíl; Pavla Havránková; Adéla Vrtková; Kateřina Slabá; Jana Tučková; et al. (MDPI AG, 2023)
Paediatric inflammatory multisystem syndrome temporally associated with COVID-19 (PIMS-TS) is a new disease in children and adolescents that occurs after often asymptomatic or mild COVID-19. It can be manifested by different clinical symptomatology and varying severity of disease based on multisystemic inflammation. The aim of this retrospective cohort trial was to describe the initial clinical presentation, diagnostics, therapy and clinical outcome of paediatric patients with a diagnosis of PIMS-TS admitted to one of the 3 PICUs. All paediatric patients who were admitted to the hospital with a diagnosis of paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) during the study period were enrolled in the study. A total of 180 patients were analysed. The most common symptoms upon admission were fever (81.6%, n = 147), rash (70.6%, n = 127), conjunctivitis (68.9%, n = 124) and abdominal pain (51.1%, n = 92). Acute respiratory failure occurred in 21.1% of patients (n = 38). Vasopressor support was used in 20.6% (n = 37) of cases. Overall, 96.7% of patients (n = 174) initially tested positive for SARS-CoV-2 IgG antibodies. Almost all patients received antibiotics during in-hospital stays. No patient died during the hospital stay or after 28 days of follow-up. Initial clinical presentation and organ system involvement of PIMS-TS including laboratory manifestations and treatment were identified in this trial. Early identification of PIMS-TS manifestation is essential for early treatment and proper management of patients.